Respuesta :

Answer:

-2,-1

Step-by-step explanation:

Solve the following system:

{y = 3 x + 5 | (equation 1)

x = -2 y - 4 | (equation 2)

Express the system in standard form:

{-(3 x) + y = 5 | (equation 1)

x + 2 y = -4 | (equation 2)

Add 1/3 × (equation 1) to equation 2:

{-(3 x) + y = 5 | (equation 1)

0 x+(7 y)/3 = -7/3 | (equation 2)

Multiply equation 2 by 3/7:

{-(3 x) + y = 5 | (equation 1)

0 x+y = -1 | (equation 2)

Subtract equation 2 from equation 1:

{-(3 x)+0 y = 6 | (equation 1)

0 x+y = -1 | (equation 2)

Divide equation 1 by -3:

{x+0 y = -2 | (equation 1)

0 x+y = -1 | (equation 2)

Collect results:

Answer: {x = -2 , y = -1

ACCESS MORE